Kelet-Közép-Európa országainak versenyképessége - Juhász, Krisztina (Közép-Európai Közlemények, 2013)
The paper analyses the competitiveness of the Central and Eastern European countries. The main goal of these analyses is to show the differences in the competitiveness of the countries in this region. In the first part of the paper we can read some interpretations of the competitiveness in several dimensions. The main question is: what does it mean and how can we measure the competitiveness of a country. The second part is about the meaning of Global Competitiveness Index, published in the Global Competitiveness Report by the World Economic Forum. The third part talks about the competitiveness of Central and Eastern European countries. The main consequences of these analysis are: 1. Although the countries of the regions have reached the efficiency0driven stage of the development, there are still serious problems with the basic requirements, mainly with the institutions (just like burden of government regulation, transparency of government policymaking) and in some countries (just like Romania) with the infrastructure. 2. Some parts of the goods market and of the labor market efficiency (just like extent and effect of taxation) also belong to the most problematic factors in the regions. 3. The advantages of the countries in the regions are very heterogenic: mainly the education and in some countries in transition from the efficiency driven to the innovation drives stage the innovation capacity can be the basis of the next stage of the development.